(untitled) (Economics and region, 2024)
The article analyzes the impact of technological factors on the labor market, namely on unemployment. Structural unemployment is singled out as the one that is most affected by modern technologies. The ways of empirical identification of structural unemployment are analyzed. An econometric model is formed that reflects the impact of technology on structural unemployment in some developed countries over the past 11 years. It is found that this impact is inverse and that not all indicators of technological development have an impact on unemployment. The reason for this is frictional unemployment, as well as the social policy of developed countries. The author also calculated the share of the unemployed who have not worked for more than a year and formed a correlation matrix, which, however, did not reveal a correlation between this indicator and indicators of the level of technological development. Thus, it is not appropriate to distinguish structural unemployment due to its duration. Conclusions are drawn about the impact of technological factors on structural unemployment. This influence is inverse, which proves the hypothesis that technology creates more jobs than it eliminates. However, technology is not recognized as a determining factor affecting the unemployment rate.